Validity and Reliability of the Persian Version of Leeds Dyspepsia Questionnaire: - Masjedi Arani, Abbas; Batebi, Sepideh; Jafari, Mahdi; Sadeghi, Amir; Saberi Isfeedvajani, Mohsen; Davazdah Emami, Mohammad Hassan (Galen Medical Journal, 2019)
Background: It is essential in clinical care services to measure the symptoms of functional dyspepsia both in the primary examination and treatment outcomes. No valid assessment tool is already available for functional dyspepsia in Iran. The present study aimed at evaluating the reliability, validity, and responsiveness of the Leeds dyspepsia questionnaire (LDQ). Materials and Methods: The LDQ was completed by 67 subjects with no dyspepsia symptoms and 93 subjects with certain functional dyspepsia diagnosed via endoscopy by a gastroenterologist and other clinical assessments. After definite diagnosis of functional dyspepsia, the participants were assessed by the LDQ. The psychometric characteristics of the questionnaire were then documented to investigate its reliability, validity, and responsiveness. Results: The internal consistency of the LDQ ranged from 0.80 to 0.89 and its test-retest reproducibility was 0.96. The LDQ was significantly correlated with all domains of dyspepsia symptom severity index (DSSI) and also with some of the domains of gastrointestinal symptom rating scale (GSRS). The LDQ had a sensitivity of 90.3% with a great specificity and a very good predictive validity. Moreover, a significant responsiveness to changes was observed (P<0.05). Conclusion: The LDQ is a valid, reliable, reproducible, and self-rated instrument responsive to change, which can be used to measure the frequency and severity of functional dyspepsia symptoms in clinical trials. [GMJ.2019;8:e1609]Â 